Analisis Pengaruh Personalisasi Berbasis AI terhadap Niat Beli Konsumen Generasi Z di Shopee melalui Persepsi terhadap Personalisasi - Diva Aryana, I Kadek; Adhiswari Wedagama, Dewa Ayu Trisna (Economic Reviews Journal, 2025)
This study aims to analyze the effect of artificial intelligence (AI)-based personalization on Generation Z consumers’ purchase intention on Shopee through perceived personalization as a mediating variable. This research employed a quantitative approach using a survey method involving 120 Generation Z respondents who actively use Shopee. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that AI-based personalization has a positive and significant effect on purchase intention. Perceived personalization also has a positive and significant effect on purchase intention and plays a mediating role in the relationship between AI-based personalization and Generation Z consumers’ purchase intention. This study highlights the importance of AI-driven personalization strategies in enhancing consumer engagement and purchase intention in e-commerce platforms.